Pengaruh Pemberian Seduhan Daun Sirih terhadap Lama Penyembuhan Luka Perineum Ibu Nifas di PMB Endang Pasar Minggu Jakarta Selatan - Endang Sri Sayekti; Rina Sri Widayati (The Journal General Health and Pharmaceutical Sciences Research, 2024)
perineal injury in puerperal mothers refers to tears that occur in the birth canal, both caused by Labor and episiotomy. This tear can occur spontaneously or through an episiotomy. Perineal care is important to prevent infection, as inadequate care can lead to infection, which is one of the causes of postpartum maternal death. Based on this, the researchers tried an alternative by using betel leaf steeping to accelerate the healing of perineal wounds. This study aims to determine the effect of betel leaf steeping on the duration of perineal wound healing in puerperal mothers in PMB Endang Pasar Minggu, South Jakarta. this study uses a quantitative approach with Pre-Experimental design and One-Shot Case Study. The sampling technique used was consecutive sampling, with a total of 20 participants. research shows that most postpartum mothers experience rapid perineal wound healing after receiving treatment with betel leaf steeping. The one sample proportion test revealed that 60% of respondents experienced a decrease in perineal injuries after being given betel leaf steeping. there is an effect of betel leaf steeping on long-term perineal injury in puerperal mothers in PMB Endang Pasar Minggu Jakerta Selatan.